Efficiency enhancement of copper indium gallium di-selenide thin film solar cell using optimized material propeties - Khoshsirat, Nima (2014)
The Copper Indium Gallium di-Selenide (CIGS) thin lm solar cells are studied in this research. The interest in Cu (In1 x, Gax) Se2 thin lm solar cells has increased significantly due to its promising characteristics for high performance and low cost. The cell structure consists of a substrate that is made of glass and layers of back contact, CIGS absorber, buffer, window layer and front contact. The material that was used as the buffer layer in this study is the Indium Sulphide as an alternative to the conventional toxic material, Cadmium Sulphide. The geometrical, electrical and optical properties of each layer can affect the cell performance and efficiency. The objective of the research is to find and propose the optimum thickness and electro-optical properties of absorber, buffer and window layer. The electro-optical parameters that are studied in this project are the energy band gap (Eg), electron affinity (_e), light absorption coefficient (_) and doping density. In this project the performance of (CIGS) thin _lm solar cell has been numerically simulated using the simulation program called SCAPS-1D. The simulation started on a baseline model that was proposed by Gloeckler et al. This is the most valid model of CIGS thin _lm solar cell that serves an excellent starting point for more specific and more complete simulations. The Gloeckler model contains the initial values for the material properties of each layer. These values were used as the simulation starting points. Since the material that are used in a CIGS thin lm solar cells all are compound semiconductors, their properties are the function of their composition. In the other words, the electro optical properties of the compound semiconductor materials can be tuned in a specific range. Accordingly, in this study first the major material properties of each layer were extracted in a range from valid references which experimentally studied the electro-optical features of the materials. This made the present research as an empirical study which is based on values that are experimentally measured. It is important to be mentioned that in some cases interpolation was done by curve fitting technique to reach to some unknown values of material properties. Then the numerical simulations are performed by varying the eometrical, electrical and optical properties for each layer in the extracted range. The effects of these variations on cell performance were investigated and data analyses were done in order to find the optimum ranges for layers properties. Resulting optimized cell shows 20.16% efficiency with the Voc=0.762 V; Jsc=32.28 mA/cm2; FF=81.99%. This is comparable with the highest reported efficiency for a laboratory scale CIGS/In2S3/i-ZnO/ZnO:Al solar cell that is 16.4% and Voc=0.665 V; Jsc=31.5 mA/cm2; FF=78%. At the last step the best reported CIGS/In2S3/i-ZnO/ZnO:Al cell in the literature was simulated to find the value of its absorber and window layer band gap. The simulation result is in a good agreement with the reported experimental study results. The obtained optimized material properties can be used in fabrication of the cell with optimized and desired features and give faster input to the fabrication process.